2020
DOI: 10.5267/j.msl.2020.4.007
|View full text |Cite
|
Sign up to set email alerts
|

The antecedent model of green awareness customer

Abstract: This study aims to review the correlation of environmental knowledge, eco-label, and perceived quality of green awareness customers with environmentally friendly products. Research method is based on a survey on 100 customers of a supermarket who are familiar with environmentally friendly products. The analysis technique conducted uses linear regression with smart tools of SPSS for testing the hypotheses of the paper. The research finding demonstrates that environmental knowledge, eco-label, and perceived qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
7
6
1
Order By: Relevance
“…Hypothesis H3, which indicates that GAD influences the consumption of green products by the millennial generation, is accepted. This finding supports the idea that millennials focus their attention on advertising messages from companies about the eco-features of organic products [48,55,56]. This corroborates that consumers exposed to GAD shape their attitudes in favor of the environment [42,43].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Hypothesis H3, which indicates that GAD influences the consumption of green products by the millennial generation, is accepted. This finding supports the idea that millennials focus their attention on advertising messages from companies about the eco-features of organic products [48,55,56]. This corroborates that consumers exposed to GAD shape their attitudes in favor of the environment [42,43].…”
Section: Discussionsupporting
confidence: 83%
“…This supports the finding that the GAD raises consumer awareness and stimulates their environmental awareness to encourage them to purchase organic products [48,50]. This finding supports the results of other research that has identified a positive relationship between green advertising and environmental awareness [37,38,55,56,66,67] and contradicts the positions of research that has determined that GAD does not stimulate the EAW of consumers who consume organic products [13,61].…”
Section: Discussionsupporting
confidence: 80%
“…One of the most applied GM practices by companies is green advertising, which is used to publicize the qualities of green products and their benefits of use; it is also used as a means to promote good practices in favor of environmental conservation [8,40]. Another GM practice is the use of eco-labels, whose design and information seek to visually impact the green qualities of the products to influence the purchasing decisions of consumers [41,42]. Similarly, another common practice is focused on continuous improvements associated with sustainability, which increases the perceived value of the product and positively impacts consumer purchasing decisions [43].…”
Section: Green Marketing (Gm)mentioning
confidence: 99%
“…Bitner's various studies examine the relationship between green consumers and other factors like purchasing intentions, customer satisfaction, preferences, and brand loyalty. The research by Alamsyah and his colleagues [27] pays attention to the urban hotels that have been successful due to the in-depth understanding of how green customers develop their purchasing intentions and make decisions to consume products and services from a specific brand. This group of consumers has an outstanding feature in developing their purchasing intentions from environmentally appealing and protection activities [28].…”
Section: Previous Studies On Relationships Between Green Customers and Other Factorsmentioning
confidence: 99%
“…According to some studies on green customer behavior, satisfaction also depends on the importance given to the environment. It primarily influences purchasing from a given brand despite other substitutes and closely related firms in the same industrial category [27]. A change in consumer lifestyle towards environmental sustainability is directly proportional to their satisfaction with the goods and services they access from various hotels.…”
Section: Previous Studies On Relationships Between Green Customers and Other Factorsmentioning
confidence: 99%